Penerapan Blended Learning Dalam Upaya Menunjang Pembelajaran Abad 21 - Ersya Pricyliana; Desy Safitri; Sujarwo Sujarwo (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
21st-century learning always goes hand in hand with technology. Technology will always be involved in learning, and teachers are required to look for alternatives if learning experiences obstacles. The Covid-19 pandemic has hampered face-to-face learning. Therefore, teachers apply the blended learning model as a solution to combine online and offline learning. This research aims to find out how blended learning is implemented in elementary school to high school education. This research uses a literature study method by searching for various related reference materials. The results of the research show that the application of the blended learning model in education produces significant and positive results in student development.